Tax Governance in the NFT Ecosystem and Metaverse - Nur Sandi Marsuni (Journal GoodWill, 2022)
Background:Metaverse, popular since 2020, blurs the lines between the real and virtual worlds. Transactions in the metaverse involve Augmented Reality (AR), Virtual Reality (VR), and virtual currency, creating new needs for tax policies. Currently, tax regulations only cover crypto payments, not comprehensively covering all transactions in the metaverse. Objective: This research aims to formulate a tax policy model for the entire series of transactions in the metaverse, including Non-Fungible Tokens (NFT). Method: This research uses the Systematic Literature Review (SLR) method, reviewing various literature sources and related regulations to formulate a tax imposition model for metaverse transactions. Results: The research found that the metaverse involves complex interactions and transactions between subjects, objects, and payment media. Currently, only crypto assets have tax regulations through PMK No. 68/PMK.03/2022. NFTs, which have nonfungible characteristics, are interchangeable with cryptocurrencies, and NFT transactions may be taxed similarly to cryptoassets. Conclusion: Taxation of NFTs in the metaverse can be carried out on transactions that produce commodity flows as a payment medium. Tax rates follow real-world regulations tailored to the NFT object. In buying and selling NFTs there is a 0.1% PPh, in exchange there is a 5% PPh and 11% VAT, and in rentals there is a 2% or 10% PPh depending on the type of asset. This research is limited to existing literature and regulations, with the implication of the need to identify potential further tax policies on crypto assets and the metaverse.